Effects of a traditional agricultural sector’s decline in less favoured areas - Bittner, Beáta; Kerékgyártóné Mislovics, Anita (Acta Agraria Debreceniensis, 2012)
Due to the effects of economic and political transformations, privatization and accession to the EU, Hungarian agriculture has gone through significant changes in the last two decades. As a result of continuous changes in the economic and regulatory environment, producers have to plan and maintain cultivation and adapt to the changing market needs within continuously changing circumstances. These effects have resulted in a significant decline or in some cases, certain sectors have disappeared. These exercise a negative social and economic effect on all over the country, causing irreversible damages on those regions where agriculture is the only source of living. This paper discusses the effects of breakdown or disappearance of a traditional agricultural sector, namely the tobacco sector.